الإظهار والإدغام بين القراء الحجازيين والكوفيين وعلاقتهما بلهجات العرب نافع والكسائي أنموذجا - صباح, قصير; نور الدين, مهري (جامعة الوادي - University of Eloued, 2021)
يسعى هذا المقال إلى الوقوف على أثر اختلاف اللهجات العربية في القراءات القرآنية، ممثلا لذلك بظاهرتي الإظهار والإدغام، وهما ظاهرتان اشتهرت أولاهما على لسان الحجازيين،بينما فشَت الثانية على ألسنة التميميين، وقد وقع اختيارنا على قارئين مشهورين؛ يمثل كل منهما لهجة تختلف عن الأخرى في بعض الظواهر اللغوية، وهما نافع المدني(ت169ه) والكسائي الكوفي (ت189ه)، وتبين لنا من خلال عرض هذا المقال أثر الاختلاف اللّهجي في القراءات القرآنية، ممثَّلا في هاتين الظاهرتين الصوتيتين، بحيث ثبت من خلال استعراض قراءة كل من القارئين أن نافعا يميل إلى الإظهار، كما هو الحال في لهجة قومه، بينما كان الكسائي يختار الإدغام، موافقا للهجة قبيلته وبلده. This article seeks to examine the impact of different Arabic dialects on the Quraanic recitations, represented by the phenomena of manifestation and compulsion. The first was known by the Hijazis, while the second was known to the Tamimites. We have chosen two well-known reciters each of them represents a dialect that differs from the other in some linguistic phenomena, namely Nafie Al-Madani (d.169 AH) and Al-Kisay Al-Kufi (d.189 AH). By presenting this article, we can see the effect of the dialectical difference in the Quraanic recitations, represented by these two phonological phenomena. It was proved through reviewing the reading of each of the reciters that Nafie tends to the manifestation, as is the case in the dialect of his nation, while Al-Kisay choses the assimilation in accordance with the dialect of his tribe and his country.
مقال
Keywords: الإظهار ; الإدغام ; الكوفة ; الحجاز ; نافع ; الكسائي; manifestation ; assimilation ; al-kufa ; al-hijaz ; nafie ; al-kisa